Varied promotion effects and mechanisms of biochar on anaerobic digestion (AD) under distinct food-to-microorganism (F/M) ratios and biochar dosages. (1st January 2023) - Chen, Yuqi; Wang, Yuzheng; Xie, Hongyu; Cao, Wenzhi; Zhang, Yanlong
Graphical abstract: Highlights: The promotion of CH4 yield from biochar was stronger at higher FM ratio. Biochar promoted anabolism as well as catabolism of anaerobes. The dominant methanogenic pathway shifted due to increasing biochar dosage. Biochar enriched Acinetobacter which enhanced the VFA degradation. Excessive biochar triggered excess biomass growth and thus decreased CH4 yield. Abstract: Biochar (BC) promotes the performance of anaerobic digestion (AD) through different routes, such as enriching microbes, buffering pH and promoting electron transfer. However, the mechanisms and processes of AD that enhanced by BC under various food to microorganism (F/M) ratios are still unclear. The organic transformations, bioelectrochemical characteristics and microbial consortia under the different BC dosages and F/M ratios were studied to reveal the role of BC in an AD process. The electron transfer system (ETS) was proportional to BC dosage and considered to be a key for AD promotion. At the F/M ratios of 0.5 and 1.0, BC accelerated methane production mainly by promoting ETS. The most enhanced specific methanation activities (SMAs) were obtained with 10.0 g/L BC, and the promotion efficiency under the F/M ratio of 1.0 was significantly higher (P < 0.05) than that under the F/M ratio of 0.5. Under the higher F/M ratio of 2.0, BC shortened the entire AD duration for 5.0 ∼ 13.0 days and guaranteed the resilience of AD by expanding the thermodynamic window of syntrophic methanogenesis via direct interspecies electron transfer (DIET). The COD balance analysis and the ecological functional profiles of microbes demonstrated that BC promoted both the anabolism and catabolism of anaerobes, and enhanced the DIET by converting hydrotrophic methanogenesis into acetolastic methanogenesis pathway. Besides, excessive BC enhanced SMA and simultaneously triggered superfluous biomass growth and thus decreased CH4 yield. This study provided an important reference for further application of BC under various F/M ratios and dosages in AD.